'Los esqueletos oxidados de los buques hundidos en la guerra': Tracing the Spanish Civil War and Barcelona's Expansion in Carmen Laforet's Nada. Issue 9 (20th October 2020) - Cohn, Adam
Abstract: The present article argues that the presence of the Spanish Civil War in Carmen Laforet's Nada (1945) is much more pervasive than previously asserted in criticism on the novel. I maintain that when references to the war are read alongside the biographies of the characters, an allegorical interpretation of the rise and fall of modern Barcelona leading up to the main action of the novel emerges. As one of Michel de Certeau's 'walkers', Andrea inscribes this politicized, alternative history of Barcelona in her perception of the city's topography through the presence of specific place markers, such as the Eixample, Montjuïc, the Barrio Chino, and the Via Laietana. Furthermore, the representations of these landmarks, streets, and neighbourhoods, when interpreted contextually, bolster this politically-pointed reading of the novel. In a final analysis, the combination of these two approaches to Laforet's work emphasizes how Andrea's evolving subjectivity inherently casts doubt on the nascent regime's rhetorical claim of control over time and place.